Ludo Media Collaborative Fraction to Improve the Collaboration Skills of Grade IV Students - Siti Raihani Vesya; Kufita Rachman; Ni Putu Miranda Puteri; Ade Putri Arbiyanti (AlphaMath : Journal of Mathematics Education, 2025)
Collaboration is a critical 21st-century skill that supports learners in navigating complex academic and social challenges. This study introduces Dokocah (Fraction Collaboration Ludo), an innovative educational medium designed to enhance collaboration skills among fourth-grade students during mathematics instruction on fractions. Addressing the urgent need for engaging, skill-oriented learning tools in elementary education, this research adopts the ADDIE Research and Development model, encompassing analysis, design, development, implementation, and evaluation phases. Data were collected through interviews and questionnaires, then analyzed using descriptive qualitative and quantitative methods. The validation process yielded high feasibility ratings: 91.3% for material and 87% for media. The practicality assessment showed strong student approval (85.5%). Effectiveness testing revealed a significant improvement in the experimental group (N-Gain = 0.71, “High”) compared to the control group (N-Gain = 0.26, “Low”), with a statistically significant difference confirmed by an independent sample t-test. These findings indicate that Dokocah is a feasible, practical, and effective tool for improving collaboration skills, thereby supporting students in mastering key competencies such as communication and social responsibility essential for 21st-century learning.